Determination of Trace and Minor Metals in Benign and Malign Human Thyroid Tissues - Kaya, Gokce; Avci, Halim; Akdeniz, Ismail; Yaman, Mehmet (Asian Journal of Chemistry, 2009)
There is a need for the analysis of essential and toxic metals in cancerous and non-cancerous human thyroid tissues because the relationship between these elements and the mechanism of cancer development and inhibition were reported in the literature. Selected metal concentrations including Ni, Fe, Mg and Ca in both cancerous (malign) and non-cancerous (benign) thyroid tissues were determined by atomic absorption spectrometry. For this purpose, wet tissues were digested by using microwave energy. The calcium concentrations in the malign thyroid tissues were found to be lower significantly than in the benign thyroids. It was observed that there are slightly the reverse-proportional relationship between the changes in iron concentrations and the changes in nickel concentrations regarding cancerous and non-cancerous thyroid samples. Therefore, it is understood that the decreases in the calcium levels in the cancerous thyroid samples in compared to non-cancerous tissues and the interaction between nickel and magnesium are very important for the investigation of cancer mechanism and may be important for cancer diagnosis.
Keywords: Cancer; Metals; Human thyroid; Microwave energy; Atomic absorption